THE IMPORTANCE OF FOLK SONGS IN YOUTH EDUCATION - Rakhimov R. N. (Web of Journals Publishing, 2024)
The article examines the role of folk songs in the upbringing of the younger generation, emotional experiences, human qualities,spiritual world, deep philosophical and Social Thought, and the valuable thoughts of Eastern thinkers Al-Farabi, Ibn Sina, Abdurahman Jami, Alishep Nawai about the interaction of musical education with moral education, about the spiritual maturity of the individual.
Keywords: folklore, music, elegance, musical sound, morality, character, balance, classical, national decoration, elegant, large, small.